预紧力对滚珠丝杠副摩擦力矩波动的影响分析及试验 - 康献民; 傅卫平; 王大承; 王建生; 王世君 (Jixie chuandong)
Based on the model of ball screw’s balls and nut raceway under the load of preload force,a andysis method of the force is proposed when the ball is pushed into and out of the raceway,and computing model of ball screw friction torque fluctuation is deduced.Effects of ball screw parameters on its friction torque is analyzed father.The test results indicated that friction torque fluctuation arises along with the preload force increment and its frequency responds to the frequency of ball pushed into and out of the raceway.